2019
DOI: 10.3389/fphys.2019.00254
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Advanced Imaging Techniques for the Characterization of Oily Skin

Abstract: Excessively oily skin leads to clinical signs that cause discomfort to patients, such as excessive shine, enlarged pores, acne, and an imbalance of the hydrolipidic layer. In this context, a constant demand for the research and development of products that prevent these features, has been noted in the field of cosmetics and dermatology. Thus, the objective of this study is to evaluate the cutaneous characteristics of oily skin due an excessive production of sebum through biophysical and skin imaging techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 29 publications
(32 reference statements)
1
47
2
5
Order By: Relevance
“…Thus, greater brightness detected by the equipment means greater uniformity of the skin surface evaluated. A recent study by Melo & Maia Campos 23 showed that the malar region has a larger number of pores than other regions, with this parameter being correlated with changes in skin microrelief such as skin roughness (Rt) and texture (SEr). Thus, this type of skin had a less uniform microrelief.…”
Section: F I G U R Ementioning
confidence: 99%
“…Thus, greater brightness detected by the equipment means greater uniformity of the skin surface evaluated. A recent study by Melo & Maia Campos 23 showed that the malar region has a larger number of pores than other regions, with this parameter being correlated with changes in skin microrelief such as skin roughness (Rt) and texture (SEr). Thus, this type of skin had a less uniform microrelief.…”
Section: F I G U R Ementioning
confidence: 99%
“…According to the ban on animal testing for many products, nowadays the human model has been developed and accepted for comedogenic testing of finished products. Comedones counting can be performed by various skin imaging techniques and correlated to skin surface characteristics (microrelief) [ 6 ]. The principle of the comedogenic testing on the human model is to investigate the level or number of microcomedones after applying the designed amount of the tested product on the back of subjects with comedone prone skin.…”
Section: Discussionmentioning
confidence: 99%
“…Qualquer alteração, seja na função ou até mesmo na estética da pele, tem como consequência problemas para a saúde física e mental do indivíduo em questão e por esse motivo, a preocupação com a estética aumentou muito na última década. A manutenção da viscosidade, integridade e aspecto da pele, vem se tornando cada vez mais uma procura constante em todo o mundo (CAMPOS MPMBG, et al, 2019;EICHENFIELD LF, et al, 2010).…”
Section: Introductionunclassified